Rejuvenated Circulating Endothelial Progenitor Cells and Nitric Oxide in Premenopausal Women with Hyperhomocysteinemia. (4th November 2020) - Peng, Long; Gu, Qianlin; Huang, Zhenhua; Zeng, Lijin; Chu, Chang; Yang, Xiaoan
Abstract : Hyperhomocysteinemia (HHcy) induced endothelial dysfunction is associated with disturbance in circulating endothelial progenitor cells (EPCs). Nevertheless, whether this unfavorable effect of HHcy on circulating EPCs also exists in premenopausal women is still unknown. Therefore, this leaves an area for the investigation of the difference on the number and activity of circulating EPCs in premenopausal women with hyperhomocysteinemia and its underlying mechanism. The number of circulating EPCs was measured by fluorescence-activated cell sorter analysis, as well as DiI-acLDL and lectin fluorescent staining. The migration and proliferation of circulating were evaluated by the Transwell chamber assay and MTT. Additionally, the endothelial function and levels of nitric oxide (NO), VEGF, and GM-CSF in plasma and culture medium were determined. The number or activity of circulating EPCs and flow-mediated dilatation (FMD) in premenopausal women with or without HHcy were higher than those in postmenopausal women. However, no significant effect of HHcy on the number or activity of circulating EPCs in premenopausal women was observed. A similar alteration in NO level between the four groups was observed. There was a correlation between FMD and the number or activity of EPCs, as well as NO level in plasma or secretion by EPCs. For the first time, our findings illuminated the quantitive or qualitative alterations of circulating EPCs and endothelial function in premenopausal patients with HHcy are preserved, which was associated with retained NO production. The recuperated endothelial repair capacity is possibly the potential mechanism interpreting cardiovascular protection in premenopausal women with HHcy.